Без жалости: [роман] / Том Клэнси ; [пер. с англ. И. Почиталина] - Клэнси Том (Эксмо, 2006)
Экземпляры: ЦБ (20140216) / Инвентарный номер: 46388 / Цена: 200.00 / Авт.знак: К 51 / ГРНТИ: 17.82 / ББК: 84(7Сое)